2022
DOI: 10.1155/2022/8086793
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Dietary Diversity Practice among Pregnant Women in the Gurage Zone, Southern Ethiopia, 2021: Community-Based Cross-Sectional Study

Abstract: Background. Dietary diversification is considered the proxy indicator of dietary quality and nutrient adequacy during pregnancy. Pregnant women have been considered susceptible to malnutrition because of their increased nutrient demands and thus consuming a variety of foods in their diet plays a lion’s role in ensuring adequate nutrient intake. So understanding bottleneck factors associated with dietary diversity practice is very crucial to encouraging adequate dietary diversity practice. Therefore, this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Ethiopia. The results showed that 38.4% of pregnant women in the study area had optimal dietary diversity practices, which is in line with a community-based study in southern Ethiopia, where the magnitude of optimal dietary diversity was 42.1% (Gudeta et al, 2022). However, our finding was higher than another report from Gurage Zone, southern Ethiopia (Geta et al, 2022).…”
Section: F I G U R Esupporting
confidence: 89%
“…Ethiopia. The results showed that 38.4% of pregnant women in the study area had optimal dietary diversity practices, which is in line with a community-based study in southern Ethiopia, where the magnitude of optimal dietary diversity was 42.1% (Gudeta et al, 2022). However, our finding was higher than another report from Gurage Zone, southern Ethiopia (Geta et al, 2022).…”
Section: F I G U R Esupporting
confidence: 89%
“…( 7 ) This discrepancy might be due to variations in the study period, geographical area, socioeconomic, and reporting (hence self-reporting). But it is lower than studies conducted in Gurage zone (42.1%), ( 17 ) Hossana (42.6%), ( 18 ) Bale (44.8%), ( 19 ) Gojjam (55%), ( 14 ) Alamata (61.2%), ( 20 ) and Ghana (46 %). ( 21 ) The discrepancy may be caused by variations in how dietary diversity was measured and categorised, eating habits, and other socio-demographic factors of women that are found in various areas of the country.…”
Section: Discussionmentioning
confidence: 63%
“…In the study conducted by Merga et al in Ethiopia on women of reproductive age, women’s empowerment on purchasing foods increased DD about four-fold [ 41 ]. In other study by Gudeta in Ethiopia, the more women’s empowerment, which also contained the dimension of decision-making power, increased DD three-fold [ 42 ]. The same result was also seen in Nigeria by Voufo et al, where the increase in women’s empowerment was positively associated with DD, and it was stronger in households in which the share of women’s decision-making was higher [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of their study showed that food insecurity was negatively associated with DD; as the food insecurity score increased, the DD score decreased. Gudeta et al also reported that DD was associated with food security among the studied women [ 42 ]. This association was also shown in other studies, such as Hosseinpour in Tehran, Iran [ 53 ]; Sheikhi in Zahedan, Iran [ 6 ], in Karachi, Pakistan [ 54 ]; and Binte Ali in rural Bangladesh [ 55 ].…”
Section: Discussionmentioning
confidence: 99%